The Role of Local Government in Providing Protection and Educational Support for Female Workers in the Informal Sector - Jeni, Rima Hayatul; Syafril, Rizki (Nurul Jadid University, 2025)
This study aims to analyze the role of local governments in protecting and providing educational support to female workers in the informal sector, with a focus on those engaged in nighttime economic activities. As the number of women in the informal sector rises, they face various risks without sufficient protection, highlighting the need for government intervention. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation from government agencies and female workers in the sector. The findings reveal that the local government's role is not fully optimized. As a regulator, there are no specific local regulations to protect female workers. As a facilitator, efforts to coordinate and provide mentoring remain fragmented. In its protective role, the government's actions are limited to general socialization and security patrols without direct protection programs. As a service provider, public services fail to address the real needs of these workers. The study concludes that the local government's role needs strengthening across all areas—regulation, facilitation, protection, and service provision—through the establishment of targeted policies, improved coordination, and the creation of sustainable, needs-based protection programs to ensure the welfare and safety of women in the informal sector.